Pengaruh Persepsi Dukungan Organisasi dan Efikasi Diri terhadap Pengembangan Karier Pegawai pada Dinas Pertanian Kabupaten Aceh Selatan - Said Abul Khair; Husnaina Mailisa Safitri; Nadiya Nadiya (Lembaga Pengembangan Kinerja Dosen, 2026)
Employee career development in the South Aceh District Agriculture Office is important for improving the quality of human resources, which is influenced by perceived organizational support and employees' belief in their own abilities. These two factors play a role in encouraging employee readiness and career advancement. This study aims to determine the effect of perceptions of organizational support and self-efficacy on employee career development at the South Aceh District Agriculture Office. This study uses a quantitative approach with an associative research design. The sample consisted of 84 respondents, selected using a census technique (the entire population was used as the sample). Research data was collected through questionnaires and documentation studies. Data analysis was performed using multiple linear regression analysis, F-test, and t-test. The results showed that the perception of organizational support had a positive and significant effect on employee career development with a t-value of 4.074 > t-table 1.990 and significance of 0.000, while self-efficacy also had a positive and significant effect with a t-value of 3.708 > t-table 1.990 and significance of 0.000. Simultaneously, both variables had a significant effect on career development with a calculated F value of 116.187 > F table 3.111 and significance of 0.000. This study recommends that agencies pay more attention to policies related to organizational support and increasing self-efficacy to support the improvement of employee career development.